Centrosomal targeting of Syk kinase is controlled by its catalytic activity and depends on microtubules and the dynein motor. Issue 1 (9th October 2012) - Fargier, Guillaume; Favard, Cyril; Parmeggiani, Andrea; Sahuquet, Alain; Mérezègue, Fabrice; Morel, Anne; Denis, Marie; Molinari, Nicolas; Mangeat, Paul H.; Coopman, Peter J.; Montcourrier, Philippe
Abstract : The nonreceptor Syk kinase is detected in epithelial cells, where it acts as a tumor suppressor, in addition to its well‐established role in immunoreceptor‐based signal transduction in hematopoietic cells. Thus, several carcinomas and melanomas have subnormal concentrations of Syk. Although Syk is mainly localized at the plasma membrane, it is also present in centrosomes, where it is involved in the control of cell division. The mechanisms responsible for its centrosomal localization and action are unknown. We used wild‐type and mutant fluorescent Syk fusion proteins in live‐cell imaging (fluorescence recovery after photobleaching, total internal reflection fluorescence, and photoactivation) combined with mathematical modeling to demonstrate that Syk is actively transported to the centrosomes via the microtubules and that this transport depends on the dynein/dynactin molecular motor. Syk can only target the centrosomes if its kinase activity is intact and it is catalytically active at the centrosomes. We showed that the autophosphorylated Y130 Syk residue helps to uncouple Syk from the plasma membrane and to promote its translocation to the centrosome, suggesting that the subcellular location of Syk depends on its autophosphorylation on specific tyrosine residues. We have thus established the details of how Syk is trafficked intracellularly and found evidence that its targeting to the centrosomes is controlled by autophosphorylation.—Fargier, G., Favard, C., Parmeggiani, A., Sahuquet, A., Mérezègue, F., Morel, A., Denis, M., Molinari, N., Mangeat, P. H., Coopman, P. J., Montcourrier, P. Centrosomal targeting of Syk kinase is controlled by its catalytic activity and depends on microtubules and the dynein motor. FASEB J. 27, 109–122 (2013). www.fasebj.org